Spatial Heterogeneity of Heavy Metals Contamination in Urban Road Dust and Associated Human Health Risks - Huanping Lu; Yong Shen; Pankaj Maurya; Jing Chen; Tingyuan Li; Jorge Paz-Ferreiro (Land)
Rapid urbanization and associated transportation play a crucial role in the distribution of heavy metals in road dust, leading to serious environmental and health concerns. This study explored the concentration and spatial variability of metals, including cadmium (Cd), copper (Cu), lead (Pb), and zinc (Zn), in road dust across six urban zones in Guangdong Province (parks, educational, residential, commercial, traffic, and industrial areas). The study also evaluated the bioavailability of these metals to determine their carcinogenic and non-carcinogenic health impacts. The findings revealed significant variations in metal levels, with commercial zones having the highest concentrations of Zn 1316.1 ± 381.6 mg/kg), Cu (426.1 ± 136.7 mg/kg), and Cd (1.29 ± 0.08 mg/kg) due to the deposition of traffic emissions. The bioaccessibility of Pb, Zn, and Cd was found to be higher in the gastric phase, suggesting increased absorption potential when ingested. Children were at a significantly higher non-carcinogenic risk compared to adults, facing more than double the exposure. While the carcinogenic risk from Pb was low but notable, Cd presented minimal risk. These results highlight the need for targeted interventions, including stricter emission regulations and public health strategies, to mitigate the risks of heavy metal exposure in urban areas.